Medieval laments of the Virgin Mary : text, music, performance, and genre liminality - Kubartová, Eliška (Early social performance., 2023)
Laments of the Virgin Mary represent a devotional genre that offered its clerical and lay audiences of the High and Late Middle Ages a deeply inspiring, yet at the same time ambiguous, religious experience. Through the deeply emotional and markedly animated representation of the Passion, seen as if through the eyes of the mother of God, audiences and performers were not only reminded of the redemptive power of the Cross, but encouraged to experience Christ's sacrifice in a more personal and intimate manner. In the pious practice of imitatio Mariae, believers mirrored the sorrow of the mother through their own bodies in order to develop a kind of visceral empathy towards, and hence a deeper understanding of, the divine. --